Development of Maternal Fetal Blood Anatomy and Circulation Simulation Media to Strengthen Clinical Reasoning of Midwifery Students - Fathunikmah Fathunikmah; Ani Laila; Findy Hindratni (Education Achievement: Journal of Science and Research, 2026)
The development of maternal-fetal blood anatomy learning and circulatory simulation media is important to strengthen the clinical reasoning skills of midwifery students, especially in understanding complex physiological concepts that are difficult to explain through conventional learning methods. This study aims to analyze the development and use of anatomical imentmage media, three-dimensional cardiac simulation models, and YouTube-based educational videos in improving conceptual understanding and clinical reasoning among midwifery students. This study uses a qualitative approach with a phenomenological design involving 10-20 participants who were deliberately selected. Data were collected through in-depth interviews, limited observations, and documentation during learning activities using simulation media. The results of the study show that the simulation media developed improves students' understanding of mother-fetal blood circulation and cardiac anatomy in a more comprehensive, interactive, and contextual manner. The use of visual and audio-visual media also strengthens clinical reasoning skills by encouraging analytical and systematic thinking patterns. In addition, students report an increase in learning motivation, engagement, and interest in independent learning because the media is easier to understand and more interesting than conventional lecture methods. This study concludes that the development of technology-based simulation media contributes significantly to strengthening clinical reasoning and improving the quality of learning in midwifery education.